2017
DOI: 10.1101/193748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human olfactory cortex contributes to emotional and perceptual aspects of aversive associative learning and memory

Abstract: The role of the sensory cortex, beyond the amygdala, has been increasingly recognized in animal associative learning and memory. Here, we examined olfactory cortical plasticity in human olfactory associative learning and memory, while elucidating related changes in emotional and perceptual responses. Psychophysical and neurometric analyses were conducted across an odormorphing continuum, with the two extreme levels differentially conditioned with aversive and neutral stimuli. Conditioned odors acquired distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…The olfactory cortex refers to the classical cellular structure of nervous cortex, which is primarily involved in associative learning and memory ( 49 ). Yaniv et al ( 50 ) observed the changes in the olfactory (piriform) cortex in the odor memory task.…”
Section: Discussionmentioning
confidence: 99%
“…The olfactory cortex refers to the classical cellular structure of nervous cortex, which is primarily involved in associative learning and memory ( 49 ). Yaniv et al ( 50 ) observed the changes in the olfactory (piriform) cortex in the odor memory task.…”
Section: Discussionmentioning
confidence: 99%